1978
DOI: 10.5006/0010-9312-34.3.88
|View full text |Cite
|
Sign up to set email alerts
|

Stress Corrosion Cracking of Low Strength, Low Alloy Nickel Steels in Sulfide Environments

Abstract: Factors governing stress corrosion cracking (SCC) of low strength, low alloy nickel steels (e.g., ASTM A203 Grade E) in sulfide environments were investigated using a three point loaded bent beam specimen. Cracking occurred in both weld and base metal at low H2S partial pressures (to 0.001 atmosphere) and stress levels, but could be inhibited by a neutralizing amine (morpholine) and methanol addition as used for control of ice and hydrate formation in cryogenic gas plants. Cathodic polarization experiments sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 0 publications
0
18
0
2
Order By: Relevance
“…Several investigators have reported surface damage in the form of pits, trenches, and/or small blunt cracks when Ni-containing LAS were exposed to sour environments (Dunlop, 1978;Kaneko & Ikeda, 1988;Yamane et al, 1986;Yoshino & Minozaki, 1986). It is implicit in the papers that the depth-to-diameter ratio increases in the order those features were mentioned above; however, limits in aspect ratio to distinguish between them were not established.…”
Section: Effect Of Ni On Pitting/trenchingmentioning
confidence: 98%
See 4 more Smart Citations
“…Several investigators have reported surface damage in the form of pits, trenches, and/or small blunt cracks when Ni-containing LAS were exposed to sour environments (Dunlop, 1978;Kaneko & Ikeda, 1988;Yamane et al, 1986;Yoshino & Minozaki, 1986). It is implicit in the papers that the depth-to-diameter ratio increases in the order those features were mentioned above; however, limits in aspect ratio to distinguish between them were not established.…”
Section: Effect Of Ni On Pitting/trenchingmentioning
confidence: 98%
“…Those tests include NACE TM0177 Method B bentbeam test (NACE, 1996), and SSRT. Trenches and cracks were reported near the stress raisers of the bent-beam test by Treseder and Swanson (1968) and Dunlop (1978) in steels with Ni contents above 1-wt%. Kaneko and Ikeda (1988) reported increased tendency to trench formation in this test even in samples with 0.48-wt% Ni.…”
Section: Effects Of Plastic Deformationmentioning
confidence: 99%
See 3 more Smart Citations